Correlation of Proterozoic strata in the northwestern Canadian Shield - Fraser, J. A.; Tremblay, L. P. (Canadian Journal of Earth Sciences, 1969)
The Epworth and Goulburn Groups comprise the lowermost sequences of the Proterozoic strata exposed near the northern margins of the Slave (structural) Province of the Canadian Shield. Each group is at least 4600 m thick and underlies a distinct and separate area of not less than 13 000 sq. km.The many features common to the two groups indicate that they are correlative: (1) each lies unconformably on an Archean basement; (2) each is overlain unconformably and successively by kaolinitic sandstone, by dolomite, and by Coppermine River Group basalt and sediments; (3) each has argillite and quartzite near the base, interbedded argillite and limestone in the upper parts, and sandstone at the top; (4) each exhibits features characteristic of deposition in shallow water; (5) both occupy similar structural basins and show the same style of folding and faulting; (6) both are traversed by gabbro dikes and sills of similar age.Field relationships among the Proterozoic strata and the relation these strata bear to intrusive granite, dikes, and sills of known radiogenic age, define the Epworth and Goulburn Groups as of Aphebian age.